التحمل النفسي وعلاقته بمعدل النبض والتنفس لدى لاعبي نادي ديالى بكرة اليد باعمار (15-17) سنة - محمد, كمال جاسم; كريم, نصير حميد (Sulaimani Journal for Humanities, 2018)
Summary Turning researchers in the first section of the Introduction and the importance of the study as well as the problem of the study and the fields and the objectives of the study, either Part III methodology and sample and measures the study and a presentation and discussed the results in Part IV contained where he offered researchers in Part V results of the study and Nha that there is an inverse relationship between psychological stress and some of the variables the physiological players Diyala Sports Club hand reel and recommended by the researchers interest in the development of psychological stress among the players being of great significance in the level of achievement of the handball teams.